Lifetime exposure to cigarette smoking and the development of adult-onset atopic dermatitis - Lee, C.H.; Chuang, H.Y.; Hong, C.H.; Huang, S.K.; Chang, Y.C.; Ko, Y.C.; Yu, H.S. (British journal of dermatology (1951), 2011)
Summary Background  Adult‐onset atopic dermatitis (AD) has recently been recognized as a distinct disease entity, but its risk factors have not yet been clearly defined. Although gestational and perinatal exposure to tobacco smoking may be associated with the development of classic AD, the association between active/passive smoking and adult‐onset AD remains controversial. Objectives  To determine if exposure to smoking, including environmental tobacco smoke (ETS), is associated with the risk of adult‐onset AD. Methods  Tobacco smoking and exposure to ETS were measured in a case–control association analysis in 83 patients with physician‐diagnosed adult‐onset AD and 142 age‐ and sex‐matched controls. Results  Multiple logistic regression analyses showed that, among the potential environmental risk factors, both current and ever smoking were significant risk factors for adult‐onset AD [odds ratio (OR) 4·994 and 3·619, respectively], compared with never smoking. Also, packs per year was significantly associated with adult‐onset AD (OR 1·058, 95% confidence interval 1·028–1·089), suggesting a lifelong cumulative risk in current smokers. Moreover, nonsmokers with adult‐onset AD reported significantly more exposure to ETS. Conclusions  Early and/or current exposure to cigarette smoking may contribute cumulatively to the development of adult‐onset AD. Exposure to ETS in childhood is associated with the development of adult‐onset AD. Adults should be discouraged from smoking to prevent adult‐onset AD in themselves and their family members.